Effect of the Use of Recycled Concrete Aggregates on the Environment and Housing Construction in Huamachuco City - Elías Silupu, Jorge Wilmer (2020)
In the present research was determined the effect of using the recycled concrete aggregates (RCA) as raw material in the elaboration of concrete for the construction of houses in the city of Huamachuco. Portland cement Type I, 1/2 "and 3/4" gravel, coarse sand and aggregates of recycled concrete were used as raw material for the design of mixtures, these last replacing coarse sand and gravel in the percentages by volume of 50%, 75% and 100% respectively. Specimens of simple concrete and concrete containing RCA were prepared according to Peruvian Technical Standard 339.033, then the compression test was performed on the specimens after 7, 14 and 28 days of curing, according to ASTM C39, so the concrete containing 50% RCA showed the best compressive strength, reaching 200.18 kg/cm2. Also, it was observed that the compressive strength of the concrete containing 100% ACR after 14 days presents an almost linear tendency. Finally, the inventory for the life cycle assessment (ACV) of the concrete was elaborated, this information will serve to realize the ACV of the concrete using for that purpose the OPENLCA free software.